Exploring Changing People's Perceptions on Local Elections - Khanal, Sushil Kumar; Mabuhang, Tanka Subba (Adhyayan Journal, 2025)
The article explores changing people perceptions of political parties during local elections in Nepal, highlighting the different factors of recent socio-political changes. Following the restructuring of local governance in the 2022 elections, political parties have increased direct involvement with their communities, changing public perceptions. Using a constructivist interpretivist paradigm with multiple realities ontology, the study employs both structured and unstructured questionnaires and interviews to gather narrative experiences from the public. The research utilizes a convergent design, integrating exploratory and descriptive methods, and employs both qualitative and quantitative techniques, including interviews and focus groups, to capture diverse people sentiments across various respondents. The sampling of 120 respondent in convenience sampling reveals that educational changes, political disillusionment, and grassroots engagement are key drivers of these changing perceptions. With all these changes the people are increasingly evaluating political parties based on local issues such as infrastructure, education, health, and social equity, rather than national political manifesto. The findings indicated a growing trend toward electing leaders who are less affiliated with traditional parties, often younger and perceived as neutral. This shift reflects declining trust in established political parties and highlights the need for greater accountability and transparency. The study underscores a pivotal moment in Nepal’s democratic institutionalization, urging political entities to adapt strategically to maintain their relevance. By exploring these changing voter perceptions, the article contributes to a deeper understanding of political accountability and voter behavior in developing democracies, offering insights for policymakers and political strategists.